대학 교양 ‘한국사’의 역사와 현실 - 시기별 담론 분석을 중심으로 - 김지형 (교양교육연구, 9(4), 2015)
대학의 교양 한국사 과목을 둘러싼 시기별 담론을 정리, 분석하였다. 점차 교양과정의 중요성이 증대되는 흐름 속에서 대학 교양 한국사 강좌의 성격을 역사적 접근법에 의해 상대화, 객관화하기 위한 취지이다. 대학 교양 한국사의 부침을 기준으로 시기 구분하였는데, 크게 나누면 국책과목 시기와 민주화 이후의 시기로 대별될 수 있다. 한국현대사의 전개과정에서 대학의 교양 한국사 과목은 과거 권위주의 정권에 의한 국책과목으로서의 운영 시기는 물론, 이후 민주화 시대를 거쳐 현재에까지 이르러서도 정치권력의 필요와 이념적 활용을 위한 도구주의적 학문의 대상이었다. 한국사 과목을 매개로 정치권력이 지향하는 시대정신 혹은 이데올로기적 목표를 고취하기 위한 수단과 방편을 삼고자 하였다. 반면 한국사 교육의 또 다른 맥락은 사회와 역사에 대한 비판적 문제의식을 고양하고 민주주의에 대한 확고한 신념을 배양함으로써 사회적 인간의 완성을 도모하는 역할을 해왔다. 이같은 측면에서 최근 고교 한국사 국정화라는 정치사회적 국면에서 향후 대학의 교양 한국사 강좌가 어떤 기능과 역할을 하는 것이 바람직할지 모색할 필요가 있다. This paper organized and analyzed discourses of liberal arts studies of Korean history in Universities of each period. It aims to objectify and relativize the characteristics of liberal arts studies of Korean history in Universities with historical approach in the stream of growing liberal arts studies courses’ importance. The periods in this paper is distinguished by vicissitudes of liberal arts studies of Korean history in Universities, and can be largely divided by national policy on courses period and after democratization. Liberal arts studies of Korean history in Universities have always been instrumentally used as academic objects for needs of political powers and ideological utilization. It has not only been during the national policy on courses period by past authoritarian regime, but also after the period of democratization and up until today. As a media of Korean history courses, they pursed means to achieve the spirit of the age and ideological goals that political authorities intended. However, another context of Korean history education has been playing a role of completing social human by enhancing critical minds toward the society and history, and cultivating firm conviction to democracy. From this perspective, it is needed to consider what kind of roles the liberal arts studies of Korean history in Universities would have to play, and how they should function in accordance with the current political aspect of promoting standardization of high school history textbooks. KCI Citation Count: 1